2020
DOI: 10.1111/ibi.12905
|View full text |Cite
|
Sign up to set email alerts
|

A general scenario to evaluate evolution of grassland birds in the Neotropics

Abstract: Neotropical grassland birds are intimately tied to their habitat and form a phylogenetically diverse group that has been poorly studied from an evolutionary point of view. Here we present a brief review of the biogeographical history of Neotropical grasslands of relevance to grassland birds. Based on this review, we have formulated the most relevant hypotheses related to the diversification and evolution of Neotropical grassland birds. Several of the hypotheses tested are complementary to those that can be tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…These diverse ecosystems are shaped by complex interactions of quantity and seasonality of rainfall, fire, soil properties, herbivory, and humans both prehistorically and presently [reviewed by Kricher (2011)]. The avifaunas of tropical fire-maintained ecosystems are as distinctive as their plants (e.g., Prado and Gibbs, 1993;da Silva and Bates, 2002;Marini et al, 2009;Franchin et al, 2017;Norambuena and Van Els, 2020). Threats to avifaunas in these areas, especially Cerrado ecosystems-comprising a conservation savanna hotspot (Franchin et al, 2017)-include conversion to agriculture, especially soybeans (Kricher, 2011), and Climate change (Marini et al, 2009).…”
Section: Firementioning
confidence: 99%
“…These diverse ecosystems are shaped by complex interactions of quantity and seasonality of rainfall, fire, soil properties, herbivory, and humans both prehistorically and presently [reviewed by Kricher (2011)]. The avifaunas of tropical fire-maintained ecosystems are as distinctive as their plants (e.g., Prado and Gibbs, 1993;da Silva and Bates, 2002;Marini et al, 2009;Franchin et al, 2017;Norambuena and Van Els, 2020). Threats to avifaunas in these areas, especially Cerrado ecosystems-comprising a conservation savanna hotspot (Franchin et al, 2017)-include conversion to agriculture, especially soybeans (Kricher, 2011), and Climate change (Marini et al, 2009).…”
Section: Firementioning
confidence: 99%
“…Our mtDNA divergence times estimation, the strong genetic structure we observed, and the absence of gene flow between species suggest that the diversification of Psammolestes is not explained by recent dispersal events across corridors in the forested Amazon basin nor by the Pleistocene arc hypothesis [ 7 ]. In contrast, our results agree with a scenario of allopatric differentiation via long distance dispersal event(s) across the Amazon in the late Miocene, followed by recent local geographic expansion as suggested by the Tajimas’ D value [ 52 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Andes uplift and the formation of the Amazon Basin promoted species diversification via vicariance and/or dispersal which may be associated with climatic oscillations. Many examples from multiple organisms show the effect of such geological events in species differentiation [ 1 6 ], but only a handful show the role of geomorphology and climatic variations in the diversification of species from the seasonal dry tropical forest (SDTF) [ 7 9 ]. In tropical Americas, this ecosystem includes disjunct patches characterized by relatively low rainfall and high climatic seasonality [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three hypothetical historical connection routes between the Cerrado core domain and the Amazonian savanna enclaves have been proposed (reviewed by Norambuena & Van Els, 2020; Silva & Bates, 2002; Figure 1a): (i) West Amazonia corridors (Ribeiro et al, 2016; Silva, 1995; Webb, 1978; Werneck et al, 2012), (ii) a Central Amazonia corridor (Haffer, 1967; Ledo & Colli, 2017; Ribeiro et al, 2016) and (iii) an Atlantic coast corridor (Silva, 1995; Werneck et al, 2012). Studies with different organisms and methods have reported mixed support for each of these connection routes (Bates et al, 2003; Lima‐Rezende et al, 2019; Norambuena & Van Els, 2020; Ribeiro et al, 2016; Rocha et al, 2020; Silva, 1995), and thus it is not clear whether these routes represent mutually exclusive biogeographical histories or whether each species responded idiosyncratically to the same biogeographical history. Silva (1995) described distinct distribution patterns of South American savanna birds and proposed that each of them was a result of a historical connection between the Cerrado and the other northern savannas.…”
Section: Introductionmentioning
confidence: 99%
“…As vicariant events should affect all the biota equally, one prediction of this hypothesis is to find congruence among the area cladograms derived from phylogeographical analysis of the species inhabiting both savanna blocks (Brown & Lomolino, 1998; Ridley, 2004; Zink et al, 2000). As an alternative, and based on studies with birds and plants, it has been proposed that the disjunct distributions originated by long‐distance dispersal from the Cerrado core to the savannas north of the Amazon River (Norambuena & Van Els, 2020; Buzatti et al, 2018; Simon & Proença, 2000). A prediction of such a scenario would imply finding incongruent single‐taxon area cladograms for codistributed organisms (Brown & Lomolino, 1998; Frey, 1993; Ridley, 2004; Zink, 1996; Zink et al, 2000).…”
Section: Introductionmentioning
confidence: 99%